PENGARUH CORPORATE GOVERNANCE DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN - Maduretno Widowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2012)
The purpose of this study was to obtain empirical evidence about the impact of corporate governance and ownership structure on financial performance. Corporate governance is measured by two variables are independent commisioner board and audit committee while the ownership structure is measured by two variables of institutional ownership and managerial ownership.This study population is the entire banking companies that are not state-owned enterprises listed on the Stock Exchange during the period 2008 to 2010. Data obtained from the company’s annual financial statements in the period 2008 to 2010. By using purposive sampling, observational data obtained up to 65 observation data. Testing the hypothesis using multiple regression analysis.The results showed that an independent commisioner board and audit committee that affect financial performance.